TDABC Cost Analysis of Ocular Disorders in an Ophthalmology Emergency Department versus Urgent Care: Clinical Experience at Massachusetts Eye and Ear - Chou, Jonathan; Shah, Mahek; Watts, Amy; Gardiner, Matthew; Kaplan, Robert; Miller, Joan; Loewenstein, John I. (Journal of Academic Ophthalmology, 2018)
Purpose To perform a cost analysis comparison for managing common ocular disorders in an eye emergency department (ED) versus an urgent care setting using a time-driven activity-based cost model (TDABC) to assist physicians and staff in appropriate allocation of resources at their own institution.Design Retrospective analysis.Setting Massachusetts Eye and Ear (MEE) ED and Same-Day Services (SDS), which runs as an urgent care clinic.Population Patients diagnosed with corneal abrasions, dry eyes, conjunctivitis, and styes were identified between April 2014 and August 2015 (n = 2,408 [ED], 26 [SDS]). We determined resources used in delivery of care, which included personnel, consumables, space capacity, and equipment. Costs were identified based on time the patient spent with each resource.Main Outcome Average visit length and associated personal, space, equipment, and consumable costs.Results Average visit length was 196 and 53 minutes, respectively, primarily due to longer wait times in the ED. Personnel and space costs were higher in the ED compared with SDS ($68.92 vs. $51.37 and $24.44 vs. $12.86, respectively). This led to an overall higher total resource cost for patients seen in the ED compared with SDS ($108.41 vs. $81.53, respectively).Conclusion For common ocular disorders, total SDS costs were 25% less than ED costs at MEE primarily due to personnel and space utilization. Treating patients with nonemergent ocular problems outside the ED can lead to shorter visit times for patients as well as lower overall costs.
Keywords: cost analysis; time-driven activity-based cost model; emergency room; urgent care clinic